An Empirical Analysis of Competence, Personality, and Work Facilities as Determinants of Employee Performance at the Faculty of Engineering, University of Lampung - Sari, Rizka; Yulianto, Yulianto; Kagungan, Dian; Rifai, Ahmad (The Eastasouth Management and Business, 2025)
This study aims to analyze the influence of competence, personality, and work facilities on the performance of employees at the Faculty of Engineering, University of Lampung. The research method used was descriptive quantitative with an explanatory approach through the distribution of questionnaires to 88 respondents, which were analyzed using multiple linear regression. The results showed that the three independent variables had a positive and significant effect on employee performance. The competency variable has the most dominant influence with a contribution of 45.4%, followed by work facilities at 26.2%, and personality at 19.2%. Simultaneously, competence, personality, and work facilities have a very strong influence on employee performance with a coefficient of determination (Adjusted R²) of 0.892. These findings confirm that improving competence, strengthening personality aspects, and providing adequate work facilities are key factors in optimizing employee performance at the Faculty of Engineering, University of Lampung.